Denture base adaptation, retention, and mechanical properties of BioHPP versus nano-alumina-modified polyamide resins - Radwa Mohsen Kamal Emera; Reham Mohammed Abdallah (Tabriz University of Medical Sciences, 2021)
Background. Continuous development of denture base materials has led to the introduction of innovative alternatives to polymethyl methacrylate. The present study aimed to evaluate the mechanical properties, adaptation, and retention of alumina nanoparticles (Al2 O3 NPs) modified polyamide resin versus BioHPP (high-performance polymer) denture base materials. Methods. Four groups of specimens, one control (group I) (unmodified polyamide) and two groups (groups II and III) (2.5 and 5 wt% Al2 O3 NP-modified polyamide, respectively) versus BioHPP specimen group (group IV), were tested for surface microhardness and flexural strength. Complete dentures fabricated from 5 wt% Al2 O3 NP-modified polyamide resin and BioHPP were used to evaluate denture base adaptation and retention. Results. The higher concentration in the alumina NP-modified polyamide group (5 wt%) demonstrated significantly higher flexural strength values and insignificantly higher hardness values than the lower concentration (2.5 wt%). There was a significant increase in the BioHPP group in both flexural strength and surface hardness compared to all polyamide groups. A statistically insignificant difference was observed between the two denture base materials regarding mean misfit values of the calculated total tissue surface area and four of the total seven evaluated areas. Satisfactory and comparable retention values were observed for both denture base materials. Conclusion. BioHPP and Al2 O3 NP-modified polyamide resin could be used as a promising alternative denture base material with good adaptation, retention, and mechanical properties.